Early Bronchus-Associated Lymphoid Tissue Lymphoma Diagnosed with Immunoglobulin Heavy Chain Molecular Testing. (31st March 2016) - Li, Pen; Cheung, Lawrence; Chiu, Brian
Abstract : When extranodal marginal zone B-cell lymphoma of mucosa associated lymphoid tissue (MALT), a low grade B-cell lymphoma, arises in the lung it is referred to as bronchus-associated lymphoid tissue (BALT) lymphoma. We describe a patient with a history of Sjögren's syndrome and rheumatoid arthritis with dyspnea and imaging consistent with lymphoid interstitial pneumonia (LIP). However, while histology and immunohistochemistry lacked definitive features of a lymphoma, immunoglobulin heavy chain (IgH) polymerase chain reaction testing demonstrated B-cell monoclonality, consistent with an early BALT lymphoma.